PENERAPAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR SEJARAH PADA KELAS XI IPS 1 SMA NEGERI 3 WONOGIRI KABUPATEN WONOGIRI TAHUN 2015/2016 - Harjanti, Noor; Joebagio, Hermanu; Agung S., Leo (HISTORIKA, 2015)
This Research Classroom action research that apply in learning Problem Based Learning in History can increase interest for studying the history of class XI IPS1 SMA Negeri 3 Wonogiri 2015/2016 has been completed in three cycles. This research aims to determine the applicaton of interest learning Problem Based Learning in History can increase interest for studying the history of class XI IPS1 SMA Negeri 3 Wonogiri 2015/2016.This research method In each cycle there are four stages: planning, action, observation and reflection. The failure in the cycle will be corrected in the next cycle. The activities of teachers in learning the history of the application of learning Problem Based Learning in class XI IPS 1 SMA Negeri 3 Wonogiri in Cycle I, II and III have increased, so the final result is achieved in Cycle III.Â Student activity in learning the history of the application of learning Problem Based Learning in class XI IPS 1 SMA Negeri 3 Wonogiri in Cycle I, II and III have increased, so the final result is achieved in Cycle III. Students' interest in learning the history of the application of learning Problem Based Learning in class XI IPS 1 SMA Negeri 3 Wonogiri in Cycle I, II and III will be increased, thus achieved the final result in Cycle III students who have interest in learning history is high and very high-achieving 82.14% so in accordance with the expectation that student interest is high over 80%. Student achievement in learning the history of the application of learning Problem Based Learning in class XI IPS 1 SMA Negeri 3 Wonogiri in Cycle I, II and III have increased, so the final result is achieved in Cycle III contained 89.29% had values above the KKM or has been completed, so that the percentage of classical completeness in Cycle III is in conformity with the expectations that have reached more than 80% of the total number of students.The aplication of Problem Based Learning model can increase historycal interestÂ  and Learning achievement of student.